2016
DOI: 10.1002/lsm.22450
|View full text |Cite
|
Sign up to set email alerts
|

Short time efficacy and safety of focused monopolar radiofrequency device for labial laxity improvement—noninvasive labia tissue tightening. A prospective cohort study

Abstract: The present study demonstrates the positive effect of focused monopolar RF device for non-invasive labia tissue tightening. The treatment is effective and safe with high patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…Our results suggest that one or two treatments may be sufficient to achieve a very reasonable level of improvement in the treated conditions; however, some patients felt that they would benefit from more than four sessions. The FSFI changes exceeded the results achieved by previous studies (5,8), suggesting the investigated device is a highly efficient modality for treating impeded female sexual function.…”
Section: Discussioncontrasting
confidence: 73%
“…Our results suggest that one or two treatments may be sufficient to achieve a very reasonable level of improvement in the treated conditions; however, some patients felt that they would benefit from more than four sessions. The FSFI changes exceeded the results achieved by previous studies (5,8), suggesting the investigated device is a highly efficient modality for treating impeded female sexual function.…”
Section: Discussioncontrasting
confidence: 73%
“…Focused external monopolar radio frequency (Intima, BTL Industries Inc., Boston, MA) delivered in 4 consecutive treatments at 1‐week intervals for labia tissue tightening was safe and demonstrated a positive short time effect . Post‐treatment, this small study (n = 17) showed a significant improvement in overall sexual satisfaction.…”
Section: Methodsmentioning
confidence: 85%
“…Positioning of these energy‐based devices for the treatment of vaginal laxity, defining the ideal patient profile, requires further research . Studies on both minimally ablative fractional laser and radiofrequency, have mostly included patients with mild to moderate primary or secondary vulvovaginal laxity and associated secondary medical or sexual conditions (orgasmic dysfunction, stress incontinence, atrophic vaginitis). The panel agreed that they select a similar population for female genital treatment with energy‐based devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2). However Fistonic, et al [27] used radio frequency for the treatment of sagging on large lips, small lips and perineal region, being 4 sessions over a month, and obtained a satisfactory result even in a short period of applications. Vicariotto and Raichi [2], in their study on vaginal introitus sagging, performed the procedure with 5 radiofrequency sessions and also obtained substantial results.…”
Section: Resultsmentioning
confidence: 99%